Staff Guidance Note on the Application of the Joint Bank-Fund Debt Sustainability Framework for Low-Income Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
Low-income countries (LICs) face significant challenges in meeting their development objectives while at the same time ensuring that their external debt remains sustainable. In April 2005, the Executive Boards of the International Monetary Fund (IMF) and the International Development Association (IDA) endorsed the Debt Sustainability Framework (DSF), a tool developed jointly by IMF and World Bank staff to conduct public and external debt sustainability analysis in low-income countries. The DSF aims to help guide the borrowing decisions of LICs, provide guidance for creditors' lending and grant allocation decisions, and improve World Bank and IMF assessments and policy advice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet